2022
DOI: 10.1590/1980-220x-reeusp-2022-0082pt
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de intervenção educativa para adesão de adolescentes escolares à vacina contra o papilomavírus humano

Abstract: RESUMO Objetivo: avaliar os efeitos da intervenção educativa “Sai fora, HPV!” para aumento do conhecimento, atitude e adesão de adolescentes à vacinação contra o papilomavírus humano. Método: ensaio clínico randomizado por conglomerado, realizado em seis escolas de dois municípios cearenses, com 238 meninas. O grupo controle (n = 120) recebeu orientações rotineiras, e o grupo intervenção (n = 118), cartões-mensagem impressos sobre a vacina HPV quadrivalente. Aplicou-se inquérito conhecimento, atitude e práti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several authors of this study concluded that educational intervention should be incorporated into the health education process, in different environments, noticed that adolescents or parents/guardians showed better knowledge about HPV and its vaccine [6]. They indicated that the development of high-quality, gender-adapted educational materials should occur to provide detailed information about HPV and its potential health consequences, appoint to a low-cost and simple-to-apply measure, and logistical and financial barrier will have a minimal impact [13].…”
Section: Healthmentioning
confidence: 83%
See 2 more Smart Citations
“…Several authors of this study concluded that educational intervention should be incorporated into the health education process, in different environments, noticed that adolescents or parents/guardians showed better knowledge about HPV and its vaccine [6]. They indicated that the development of high-quality, gender-adapted educational materials should occur to provide detailed information about HPV and its potential health consequences, appoint to a low-cost and simple-to-apply measure, and logistical and financial barrier will have a minimal impact [13].…”
Section: Healthmentioning
confidence: 83%
“…2) Title: Effect of Educational Intervention for Compliance of School Adolescents with the Human Papillomavirus Vaccine. Year of publication: 2022 [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse contexto, uma intervenção educativa em saúde, voltada para escolares acerca da vacinação contra o HPV, favorece a adesão à vacinação e a continuidade do esquema vacinal, além de colaborar com as ações de cuidado na Atenção Primária à Saúde, dando enfoque à promoção à saúde de adolescentes e à prevenção de neoplasias. Destaca-se a relevância da intervenção educativa como recurso promotor de saúde, pois favorece a ação dos adolescentes como agentes ativos do cuidado (FERREIRA et al, 2022). Com isso, objetivou-se realizar revisão de literatura sobre a prevalência de vacinação contra o HPV no Brasil e qual o seu impacto na sociedade e nos serviços de saúde.…”
Section: Introductionunclassified